Karakteristik Sebaran Fitoplankton di Perairan Muara Sungai Sugihan, Sumatera Selatan - Mulyadi Mulyadi; Tengku Zia Ulqodry; Riris Aryawati; Isnaini Isnaini; Heron Surbakti (Jurnal Kelautan Tropis, 2019)
The anthropogenic activity around Sugihan Estuary might drive changes on physical-chemical factors which affect the abundance and distribution of phytoplankton in the Sugihan Estuary. The purpose of this study was to analyze the abundance and distribution of phytoplankton based on physical-chemical parameters at Sugihan Estuary, South Sumatera. Samples were taken at 18 stations in towards low tide condition. The measured parameters include light intensity, visibility, temperature, current velocity, salinity, pH, dissolved oxygen, nitrate, phosphate and phytoplankton samples. Principal Component Analysis (PCA) was used to determine the characteristic of phytoplankton distribution. We found 14 genus of phytoplankton which consist of 13 genera of Bacillariophyceae and 1 genus of Dinophyceae. The entire observation stations were classified into four groups based on abundance and the genus of phytoplankton. The phytoplankton abundance ranged between 101 cell/l to 1071 cell/l. The phytoplankton abundance and distribution are in linear correlation with light intensity, visibility, pH, dissolved oxygen, salinity and current velocity. This research could contribute on describing the water productivity level of Sugihan Estuary.    Aktivitas di perairan Muara Sungai Sugihan berpotensi mengakibatkan perubahan kondisi fisika-kimia perairan yang berpengaruh pada kelimpahan dan distribusi fitoplankton. Tujuan penelitian ini untuk menganalisis kelimpahan dan distribusi fitoplankton dalam kaitannya dengan parameter fisika dan kimia perairan Muara Sugihan, Sumatera Selatan. Pengambilan sampel dilakukan pada 18 titik stasiun dalam kondisi perairan menuju surut. Parameter lingkungan yang diukur meliputi intensitas cahaya, kecerahan, suhu, kecepatan arus, salinitas, pH, oksigen terlarut, nitrat, fosfat dan sampel fitoplankton. Karakteristik sebaran fitoplankton dianalisis dengan menggunakan Analisis Komponen Utama (PCA). Hasil pengamatan fitoplankton ditemukan sebanyak 14 genus, 13 genus dari kelas Bacillariophyceae dan satu genus dari kelas Dinophyceae. Seluruh stasiun pengamatan dikelompokkan menjadi empat kelompok berdasarkan kelimpahan dan genus fitoplanktonnya. Kelimpahan fitoplankton berkisar antara 101 sel/l hingga 1071 sel/l. Hubungan distribusi dan kelimpahan fitoplankton berbanding lurus dengan intensitas cahaya, kecerahan, pH, oksigen terlarut, salinitas dan kecepatan arus. Penelitian ini dapat berkontribusi dalam menggambarkan tingkat kesuburan perairan di Muara Sungai Sugihan Sumatera Selatan.